2021
DOI: 10.3390/asi4040078
|View full text |Cite
|
Sign up to set email alerts
|

Soft Sensors for State of Charge, State of Energy, and Power Loss in Formula Student Electric Vehicle

Abstract: The proliferation of electric vehicle (EV) technology is an important step towards a more sustainable future. In the current work, two-layer feed-forward artificial neural-network-based machine learning is applied to design soft sensors to estimate the state of charge (SOC), state of energy (SOE), and power loss (PL) of a formula student electric vehicle (FSEV) battery-pack system. The proposed soft sensors were designed to predict the SOC, SOE, and PL of the EV battery pack on the basis of the input current p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Proposed soft sensors attained higher prediction accuracy than that of the linear or nonlinear regression model and parametric structure models used for system identification with exogenous variables, autoregressive moving average with exogenous variables, output error, and Box Jenkins. The authors also revealed that the two‐layer feed‐forward neural network‐based soft sensors can be effectively utilized to monitor and predict the SoC, state of energy, and power loss profile of a formula student electric vehicle 15 . Standard conservation equations of continuity, momentum, and energy equations are used for the flowing fluid (air) domain, whereas only an energy balance was used for the cell domain.…”
Section: Techniques For Battery Coolingmentioning
confidence: 99%
“…Proposed soft sensors attained higher prediction accuracy than that of the linear or nonlinear regression model and parametric structure models used for system identification with exogenous variables, autoregressive moving average with exogenous variables, output error, and Box Jenkins. The authors also revealed that the two‐layer feed‐forward neural network‐based soft sensors can be effectively utilized to monitor and predict the SoC, state of energy, and power loss profile of a formula student electric vehicle 15 . Standard conservation equations of continuity, momentum, and energy equations are used for the flowing fluid (air) domain, whereas only an energy balance was used for the cell domain.…”
Section: Techniques For Battery Coolingmentioning
confidence: 99%
“…30 SoC represents the percentage of remaining usable power in the total capacity of a cell. 32 The heat production of the tab is caused by the resistance of the tab and the contact resistance between the wire and the tab.…”
Section: Batterymentioning
confidence: 99%
“…It is a function of state of charge (SoC), which can be referenced from 30 . SoC represents the percentage of remaining usable power in the total capacity of a cell 32 …”
Section: Governing Equations and Modelsmentioning
confidence: 99%
“…In HEVs, energy storage methods have primary and secondary energy sources [8]. e most prevalent fuel cell batteries are fuel cell-supercapacitor, battery-supercapacitor, and cell photovoltaic panels [9]. e primary energy source gives a long driving range, while the secondary energy source is only used when abrupt acceleration or braking is required [10].…”
Section: Related Workmentioning
confidence: 99%